1995
DOI: 10.1021/ja00128a006
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Antigen-Combining-Site Structures and Functions within a Panel of Catalytic Antibodies Generated against a Single Transition State Analog

Abstract: The diversity of the immune response, which can provide a panel of catalytic antibodies with varying degrees of catalytic activity and substrate specificity by immunization with a single hapten, raises the question concerning the extent to which a rationally designed hapten dictates the paratopes for catalytic function in the antigencombining site. We have investigated the biochemical properties within a panel of six hydrolytic catalytic antibodies elicited against a phosphonate transition state analog 3 and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 0 publications
1
57
0
1
Order By: Relevance
“…enzyme catalysis and reports of its involvement in antibodymediated catalysis (see, e.g., [7,[9][10][11]41]). Modification of Lys side chains by methyl acetimidate, and of His side chains (up to " 10 per IgG molecule) by DEP resulted in negligible decreases in catalytic activity and binding.…”
Section: Figure 4 Schematic Diagram Illustrating Possible Roles For Tmentioning
confidence: 99%
See 1 more Smart Citation
“…enzyme catalysis and reports of its involvement in antibodymediated catalysis (see, e.g., [7,[9][10][11]41]). Modification of Lys side chains by methyl acetimidate, and of His side chains (up to " 10 per IgG molecule) by DEP resulted in negligible decreases in catalytic activity and binding.…”
Section: Figure 4 Schematic Diagram Illustrating Possible Roles For Tmentioning
confidence: 99%
“…Most investigations have been concerned with monoclonal catalytic antibodies, and a principal objective of the early work was the demonstration of the wide range of chemical reactions for which antibody catalysts could be produced [3,4]. Currently, particular attention is being given to catalytic mechanism [5], and papers reporting kinetic, protein chemical and structural studies are beginning to appear [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Antibody 6D9 was generated by immunization with chloramphenicol phosphonate (CP-F) as a hapten, to produce an antibody capable of hydrolyzing a pro-drug of chloramphenicol monoester. [12][13][14][15] Crystal structures of 6D9 containing bound CPD-F have been solved (PDB codes: 1HYX for crystal form I and 1HYY for II). 16 Although crystallization of the antibody in complex with both the original hapten CP-F and its derivative CPD-F was attempted, only the 6D9 -CPD-F complex yielded crystals of high enough quality for determination of the structure at high resolution (1.8 Å); apparently the extra group in CPD-F (compared with CP-F) filled a void in the crystal lattice so as to improve crystal packing.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a number of studies have demonstrated that within a series of related antibodies (9)(10)(11) or enzyme mutants (12), catalytic efficiency usually increases as a function of increased affinity for a transition-state analog. Given the anticipated relationship between activity and hapten binding, we reasoned that in vitro affinity maturation of a catalytic antibody might provide a general means of increasing the catalytic efficiency.…”
mentioning
confidence: 99%